To split or not to split: (AsCCAs)-coordinated Mo, W, and Re complexes and their reactivity toward molecular dinitrogen - Eberle, Lukas; Lindenthal, Sebastian; Ballmann, Joachim (Inorganic chemistry, 2024)
Molybdenum, tungsten, and rhenium halides bearing a 2,2′-(iPr2As)2-substituted diphenylacetylene ([AsCCAs], 1-As) were prepared and reduced under an atmosphere of dinitrogen in order to activate the latter substrate. In the case of molybdenum, a diiodo (2-As) and a triiodo molybdenum precursor (5) were equally suited for reductive N2 splitting, which led to the isolation of [AsCCAs]Mo≡N(I) (3-As) in each case. For tungsten, [AsCCAs]WCl3 (6) was reduced under N2 to afford {[AsCCAs]WCl2}2(N2) (7), which is best described as a dinuclear π8δ4-configured μ-(η1: η1)-N2-bridged dimer. Attempts to reductively cleave the N2 unit in 7 did not lead to the expected tungsten nitride (8), which had to be prepared independently via the treatment of 7 with sodium azide. To arrive at a π10δ4-configured N2-bridged dimer in a tetragonally distorted ligand environment, [AsCCAs]ReCl3 (9) was reduced in the presence of N2. As expected, a μ-(η1: η1)-N2-bridged dirhenium species, namely, {[AsCCAs]ReCl2}2(N2) (10), was formed, but found to very quickly decompose (presumably via loss of N2), not only under reduced pressure, but also upon irradiation or heating. Hence, an alternative synthetic route to the originally envisioned nitride, [AsCCAs]Re≡N(Cl)2 (11), was developed. While all the aforementioned nitrides (3-As, 8, and 11) were found to be fairly robust, significantly different stabilities were noticed for {[AsCCAs]MCl2}2(N2) (7 for M = W, 10 for M = Re), which is ascribed to the electronically different MN2M cores (π8δ4 for 7 vs π10δ4 for 10) in these μ-(η1: η1)-N2-bridged dimers.
Im Zusatz zum Titel steht AsCCAs in eckiger Klammer
Gesehen am 15.05.2024